Perencanaan Instalasi Air Bersih dan Air Kotor Pada Bangunan Gedung dengan Menggunakan Sistem Pompa - Catur Budi Artayana, Ketut; Indra Atmaja, Gede (Jurnal Energi Dan Manufaktur; Vol 4, No.1 April 2010, 2012)
Construction of a building planned for the installation of clean water with clean water source comes from deep wells,with discharge of 7.5 liters / second. Installing a water tank roof is planned with the use of dirty water while using aseparate system. Installation path using the gravitational system of pipes and pumps with a slope of 1.5 to 5%. Showerpressure ± 1bar each sanitary appliance, according to the height of each floor of shower pressure greatly affect theinstallation path through the line shaft. Tank capacity of 11m3 and reach the bottom of the tank capacity reached 17.02m3. Total discharge at the pump boster used depending on the requirement that reached its peak hours of 2.44 liters /second. Vertical pipe is planned by using wet vendors, system vendors directly and dirty water which flowed into a septictank space. Sewerage can be calculated using the average value of the number of residents who use potable waterfacilities have been planned to reach capacity of 100.38 liters / day.
Keywords: Clean water, dirty water, Pipe Ven.